The influence of soft tissue biotype on the marginal bone changes around dental implants: A 1-year prospective clinico-radiological study - Pragathi Raghavendra Bhat; Srinath Lakshman Thakur; Sudhindra Sushilendra Kulkarni (Wolters Kluwer Medknow Publications, 2015)
Background: The peri-implant mucosa undergoes surgical and bacterial assaults in various stages of implant therapy, however, the literature on changes occurring in the peri-implant mucosa is minimal. This study was thus conducted to evaluate the change in the peri-implant mucosal thickness and its effect on the marginal bone levels around dental implants treated in a conventional two-stage implant therapy. Materials and Methods: A total of 36 implants were placed in 22 subjects. Two subjects dropped out. Thirty-three implants in 20 subjects were then evaluated. Initial mucosal thickness, marginal bone levels on radiographs, pain, and exudation were evaluated. All these parameters were recorded at the time of implant placement, at the time of cementation of final restoration, 6 months and 12 months post cementation/restoration. Results: The peri-implant mucosal thickness reduced from implant placement to second stage and till restorations and was statistically significant, in both the thick and thin biotypes, however, at 12 months there was a rebound of the tissue thickness, which was more in the thick biotype (P < 0.05). At 1-year follow-up, there was a reduction in the marginal bone levels, which was more in the thick biotype as compared to the thin biotype (P < 0.05). Conclusion: The mucosa at implant sites undergoes a reduction in thickness from the time of implant placement till the placement of final restorations. The placement of the final restorations and then end of active therapy leads to a rebound of the tissue thickness. Sites with thicker tissues preoperatively have a lesser bone loss and better rebound as compared to thinner tissues.